The Virtual Pharmacology Lab — A Repository of Free Educational Resources to Support Animal-free Pharmacology Teaching. Issue 1 (March 2014) - Dewhurst, David; Ward, Ross
The new repository will support pharmacology practical teaching by promoting the sharing and re-use of existing pharmacology resources